DC and RF/analog parameters in Ge‐source split drain‐ZHP‐TFET: Drain and pocket engineering technique. (19th October 2021) - Saha, Rajesh; Panda, Deepak Kumar; Goswami, Rupam; Bhowmick, Brinda; Baishya, Srimanta
Abstract: In this article, a Ge‐source is employed in split drain Z‐shaped line TFET structure (SD‐ZHP‐TFET) and named as Ge‐source SD‐ZHP‐TFET. The presence of split drain increases the tunnel width at interface of channel–drain, which reduces the ambipolar current ( I AMB ). Also, the horizontal pocket at source region and the Ge‐source boost the ON current ( I ON ) of the SD‐ZHP‐TFET. A comparative study in terms of transfer characteristic, current ratio ( I ON / I OFF and I ON / I AMB ), transconductance ( g m ), and cut off frequency ( f c ) among ZHP, SD‐ZHP, and Ge‐source SD‐ZHP TFETs are highlighted through TCAD simulator. We have reported DC and RF/analog figure of merits (FoM) for the variation in thickness of horizontal pocket ( t hp ) and doping concentration ( N hp ) in the horizontal pocket region by plotting transfer characteristic, g m, and f c for Ge‐source SD‐ZHP‐TFET. Furthermore, the impact of drain doping concentration of region 1 ( N du ) and region 2 ( N dl ) on transfer characteristic, I OFF, I AMB, g m, C gg, and f c are studied in proposed TFET. The Ge‐source SD‐ZHP‐TFET provides I ON / I OFF and I ON / I AMB in the order of 10 9 and 10 11, respectively. Moreover, Ge‐source SD‐ZHP‐TFET has maximum gm and maximum f c at higher value of t hp, N hp, N du, and N dl . It is also seen that the proposed device shows an improved RF/analog and DC characteristic even with scaling down of gate bias ( V G ). Finally, the various parameters of Ge‐source SD‐ZHP‐TFET is compared with the data exist in the literature.